2021
DOI: 10.1021/acsabm.0c01148
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Coimmobilization of Multimeric Enzyme Arrays with Enhanced Biocatalytic Cascade Performance

Abstract: Multiple enzyme coimmobilizations mimicking nature cascade enzymatic pathways have potential applications in diverse fields. We have developed a strategy for orderly coimmobilizing multienzymes by combining hierarchically self-assembled multimeric enzymes with specifically abundant polyhistidine tag affinity-mediated immobilization. Using this strategy, an ordered coimmobilization of the glycosyltransferase UGT51 mutant and sucrose synthase was constructed to realize the regeneration of costly sugar donor UDP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The SUS activity was determined in 250 μL reaction buffer containing the mixture contained 50 mM Tris–HCl pH 7.5, 10 mM UDP, and 500 mM sucrose, 10 μg protein ( Ali et al, 2021 ). After incubation for 1 h at 35°C, the reactions were terminated by heating at 95°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SUS activity was determined in 250 μL reaction buffer containing the mixture contained 50 mM Tris–HCl pH 7.5, 10 mM UDP, and 500 mM sucrose, 10 μg protein ( Ali et al, 2021 ). After incubation for 1 h at 35°C, the reactions were terminated by heating at 95°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Uridine diphosphate (UDP)-glycosyltransferases (UGTs) belongs to the largest glycosyltransferase family 1 and are capable of catalyzing glycosylation of various lipophilic molecules with the nucleotide UDP-sugars as the donor ( Schmid et al, 2016 ). Several UGTs have been exploited to alter the glycosylation patterns and sugar structures of natural products for developing potential therapeutic compounds ( Lairson et al, 2008 ; Xu and Kong, 2020 ; Ali et al, 2021 ). The conjugated glycosyl groups usually could alter water solubility, stability, and pharmacological properties of natural products ( Kren and Martínková, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, due to multipoint covalent attachment, the sulfur-containing amino acid residue, the cysteine remains unchanged at higher temperatures; it enhances the activity and stability of immobilized papain . In doing so, it appreciably simplifies the designing of the bioreactors; when individual catalysts in the selective compartments are sequentially retained by a chemical attachment to carry out the multi-enzyme reactions in cascade. , …”
Section: Introductionmentioning
confidence: 99%
“…To aid in bioconjugation, we chose to employ the SpyCatcher002/SpyTag002 system (SpyCat2/SpyTag2), a further optimized variant of the SpyCatcher/SpyTag covalent ligation technology developed by Mark Howarth. , The interaction of SpyCatcher002 with SpyTag002 results in the spontaneous formation of a covalent isopeptide bond. The SpyCatcher/SpyTag technology has been widely used for enzyme coimmobilization, and the benefits of this technology have been demonstrated. For example, Wong et al have shown improvement of the pH stability and reusability of SpyTag proteins immobilized on a SpyCatcher-PHA synthase fusion displayed on the surface of polyhydroxyalkanoate particles. However, improvements in thermostability following SpyCatcher/SpyTag-mediated immobilization to date have been mostly limited .…”
Section: Introductionmentioning
confidence: 99%